2010
DOI: 10.18632/oncotarget.14197
|View full text |Cite
|
Sign up to set email alerts
|

Introducing, OncoTarget

Abstract: Circulating tumor cells (CTCs) have attracted pretty much attention from scientists because of their important relationship with the process of metastasis. Here, we developed a size-based microfluidic chip containing triangular pillar array and filter channel array for detecting single CTCs and CTC clusters independent of tumor-specific markers. The cell populations in chip were characterized by immune-fluorescent staining combining an epithelial marker and a mesenchymal marker. We largely decreased the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…More recently, a size-based microfluidic chip for detecting single CTC and CTC clusters allowed for the detection of CTC in lung cancer patients with apparent high sensitivity and specificity when compared to healthy controls (82.7% sensitivity and 100% specificity) (12). Interestingly, the levels of CTC in stage I-II patients were lower as compared with patients in advanced stage or with local recurrence of the disease, thus reinforcing the need for high sensitive techniques for early diagnosis of lung cancer through CTC detection.…”
Section: Ctc As a Diagnostic Marker In Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a size-based microfluidic chip for detecting single CTC and CTC clusters allowed for the detection of CTC in lung cancer patients with apparent high sensitivity and specificity when compared to healthy controls (82.7% sensitivity and 100% specificity) (12). Interestingly, the levels of CTC in stage I-II patients were lower as compared with patients in advanced stage or with local recurrence of the disease, thus reinforcing the need for high sensitive techniques for early diagnosis of lung cancer through CTC detection.…”
Section: Ctc As a Diagnostic Marker In Nsclcmentioning
confidence: 99%
“…However, the use of an epithelial cell marker such as EpCam for CTC isolation might lead to an underestimation of the CTC count because of a potential loss of epithelial markers during the EMT that is a phenomenon frequently associated with the metastatic cascade (48). Methods that are more sensitive have been recently demonstrated to capture a higher number of CTC in NSCLC patients (12,49). Sensitivity of CTC detection is an important issue also for early diagnosis in high-risk patients as well as for prognostic assessment in early lung cancer.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…CTCs have already been widely used as a biomarker for the assessment of cancer prognosis and response to therapy (12). Previous studies have reported that CTC counts have an association with the prognosis and development of numerous metastatic diseases, including breast, colon, prostate and lung cancers (13)(14)(15)(16)(17). Therefore, studying CTCs may improve understanding of the potential mechanisms underlying tumorigenesis and metastasis, offer promising clinical trials for patients with metastatic cancer, and supply a target for designing effective and individualized cancer therapies.…”
Section: Introductionmentioning
confidence: 99%
“…We can assume that a sample obtained from a patient suffering from one of these tumors can contain CR cells, all sharing a CN profile with the tumor. We can further assume the CR cell count to be 10 cells per 10 mL, well within the range of published circulating tumor cell counts [6, 8, 28]. To model CR cells, one tumor profile is selected for each clone.…”
Section: Performance Of Single-cell Based Early Detection: a Virtual mentioning
confidence: 99%